Process for the preparation of polyurethane foams and combined polyethers used for the preparation of the polyurethane foams
Patent Information
- Application Number
- CN202410176650.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-02-08
AI Technical Summary
但其对导热系数的改善量有限,该技术方案下纯环戊烷体系的热导率>18.0mW/m·K
[0032]1、本发明制备方法可获得极小的泡孔直径。在常规制备聚氨酯的过程中,若想获得细小的气泡核通常需要成核剂,本领域可用的成核剂有氟类化合物(如含氟烷基醚)、碳纳米管、凝胶物质、无机氧化物颗粒等,但本申请不需要使用成核剂即可实现较好的微核作用。本发明通过空腔控制实现了对发泡过程的个性化调控,可以在不影响物料流动性和填充性的前提下,使物理发泡剂有控制的汽化并形成大量微核,最终获得极小的泡孔直径,平均孔径≤50μm。
Smart Images

Figure BDA0004702324850000091 
Figure BDA0004702324850000101 
Figure BDA0004702324850000111
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials, specifically relating to a method for preparing polyurethane foam and the combined polyether used in preparing the polyurethane foam. Background Technology
[0002] Thermal conductivity (also known as thermal conductivity coefficient) is one of the key indicators of rigid polyurethane foam, which determines the energy-saving level of end applications such as refrigerators and freezers. Further optimization of thermal conductivity based on existing technologies is beneficial for further carbon reduction and conservation. The thermal conductivity of rigid polyurethane foam is mainly affected by the matrix material, cell structure, and gas composition within the cells. Among these factors, optimizing the cell structure is one of the main methods to reduce thermal conductivity.
[0003] For example, CN1995109A, a method for producing rigid polyurethane foam, discloses a technical solution for optimizing the cell structure using nucleating agents. It uses organic fluorides as foaming additives to form fine crystal nuclei, thereby obtaining a dense and uniform cell structure. The resulting cyclopentane-based rigid polyurethane foam has a thermal conductivity of 18.3–20.8 mW / m·K. However, the additives used are toxic, have low solubility in the foaming agent, and low compatibility with combined polyether polyols, requiring repeated cyclic mixing.
[0004] For example, CN112175158A discloses a refrigerator and a rigid polyurethane foam, as well as a method for preparing rigid polyurethane foam. This method improves the cell structure by further optimizing the nucleating agent type. The nucleating agent used is perfluoro-4-methyl-2-pentene, added at a rate of 1-3 parts per 100 parts of combined polyether, which can obtain tiny and fine cells. However, its improvement on thermal conductivity is limited; the thermal conductivity of the pure cyclopentane system under this technical solution is >18.0 mW / m·K.
[0005] Therefore, in order to achieve better energy-saving and carbon-reducing effects, further research is still needed on how to reduce the thermal conductivity of rigid polyurethane foam. Summary of the Invention
[0006] The primary objective of this invention is to provide a method for preparing rigid polyurethane foam that can further reduce thermal conductivity, as well as the combined polyethers used in preparing the polyurethane foam.
[0007] The method for preparing polyurethane foam described in this application includes the following steps:
[0008] A mixture containing a polyether, a physical blowing agent, and an isocyanate is injected into a cavity for reaction. The reaction process is subject to a first control and a second control. After the reaction product is cured and molded, polyurethane foam is obtained. The physical blowing agent remains in a liquid state during the first control period, which refers to 30-60% of the fiber time from the start of the mixture injection. At the end of the first control, the pressure in the cavity is greater than atmospheric pressure. The second control is to immediately reduce the pressure in the cavity in stages at the end of the first control. The number of stages is a natural number and ≥2. The pressure is reduced to the point where the physical blowing agent can vaporize at each stage. The second control is completed before 70-80% of the fiber time of the mixture.
[0009] The fiber time described in this invention, also known as the gel time, refers to the time elapsed from the start of mixing the raw materials (including combined polyethers, physical blowing agents, and isocyanates) required for preparing polyurethane foam until a fine fibrous filament can be just pulled from the reactants with a thin rod. Typically, the fiber time has specific set values depending on the application scenario and process requirements. For example, it can be 25–75 seconds for filling in household appliances such as refrigerators, 5–18 seconds for spraying, and 70–100 seconds for pipe casting. This invention describes completing the second control before 70–80% of the fiber time, meaning the second control operation is completed before the fiber time is reached. For example, if the fiber time is 50 seconds, the second control is completed before 70% of the fiber time, i.e., 35 seconds before the start of injection; and before 80% of the fiber time, i.e., 40 seconds before the start of injection. Similarly, if the fiber time is 50 seconds, the first control is completed before 30% of the fiber time, i.e., 15 seconds before the start of injection. The present invention completes the first control before 30-60% of the fiber time and the second control before 70-80% of the fiber time, which is beneficial to the formation and uniform distribution of micronuclei and prevents pores.
[0010] During the mixing stage before the mixture is injected into the cavity, it is preferable that the physical foaming agent in the mixture is in a liquid state to facilitate thorough mixing. The method used to keep the physical foaming agent in a liquid state can be any conventional means in the art, such as temperature control and / or pressure control. Pressure control involves adjusting the pressure of the environment in which the material is located to increase the boiling point of the physical foaming agent, keeping it liquid under specific temperature conditions. Temperature control involves adjusting the temperature of the mixture to keep the physical foaming agent liquid under specific pressure conditions; however, the temperature of the mixture should not be too low to avoid increased viscosity at low temperatures, which would hinder flow. Generally, the temperature of the mixture should not be lower than 0°C. The temperature of the mixture is mainly determined by the temperature of raw materials such as the polyether and isocyanate. For example, if the temperature of the polyether is ≥5°C, it can be 5–35°C; if the temperature of the isocyanate is ≥0°C, it can be 0–25°C. The physical foaming agent can be premixed with the polyether or isocyanate, or it can be directly mixed and injected in real time using a multi-component nozzle mixing device. The polyether composition can be of conventional type or commercially available product in the art. Typically, the polyether composition consists of components such as polyols, catalysts, and foam stabilizers.
[0011] The applicant discovered through research that when the physical foaming agent remains in a liquid state during the first control period, it is necessary to reduce the crosslinking rate of the polyurethane reactants in order to form a finely distributed closed-cell structure in the polyurethane material. It is preferable to use a method that reduces the relative amount of catalyst and increases the initial material temperature to obtain a suitable reaction rate. For example, when the amount of catalyst is <3.0wt%, the temperature of the combined polyether and / or isocyanate before the mixture is formed is controlled at 40-70°C, that is, the mixing operation is carried out immediately after the temperature of the combined polyether and / or isocyanate is controlled at 40-70°C.
[0012] The method for maintaining the physical foaming agent in a liquid state during the first control period is mainly achieved through pressure control. This pressure control can be achieved by maintaining the pressure within the cavity at a fixed value, sufficient to ensure the physical foaming agent remains liquid during the first control period, such as maintaining it at any value within the range of 9–40 bar. Alternatively, the pressure within the cavity can be adjusted in real time, causing it to change according to a certain trend during the first control period. Preferably, the pressure change trend during the first control period is a gradual increase, to balance material flowability and prevent the physical foaming agent from absorbing reaction heat and vaporizing. The pressure change range can be 0–40 bar, i.e., a gradual increase within the gauge pressure range of 0–40 bar. This gradual increase can be continuous or intermittent. Continuous increases can be uniform, such as following the curve P = a1t + b (Equation I), or variable, such as a gradually decreasing and / or gradually increasing rate of pressure increase, such as following the curve P = a1t + b (Equation I). And / or according to P = a3t 2 +b (Equation III) curve change, where P is pressure, t is time, b is the initial pressure of the cavity, a1>0, a2>0, a3>0; intermittent type is usually a staged pressure increase, that is, the first control period is divided into pressure increase stages of ≥1 natural number, and there is at least one high pressure constant period between two adjacent pressure increase stages. The pressure value remains unchanged during the high pressure constant period. For example, the first control period is divided into 3 pressure increase stages and 2 high pressure constant periods, namely the first pressure increase stage, the second pressure increase stage and the third pressure increase stage, the first high pressure constant period and the second high pressure constant period. The first high pressure constant period is located between the first and second pressure increase stages, and the second high pressure constant period is located between the second and third pressure increase stages. The first, second and third pressure increase stages all adopt a continuous pressure increase method.
[0013] The maximum and minimum pressure values within the cavity at the end of the first control phase of this invention are determined based on the type of physical foaming agent used, to ensure that the physical foaming agent remains in a liquid state without affecting the flowability of the material. For example, for a foaming agent system containing cyclopentane, the pressure can be 9–36 bar; for a foaming agent system containing LBA, the pressure can be 11–40 bar; and for a foaming agent system containing a low-boiling-point foaming agent, the pressure can be 17–40 bar.
[0014] The second control described in this invention involves immediately reducing the pressure in the cavity in stages upon the end of the first control. This staged pressure reduction is an intermittent pressure reduction. For example, the second control stage can be divided into ≥2 consecutive pressure reduction stages, with at least one low-pressure constant period between adjacent consecutive pressure reduction stages. During the low-pressure constant period, the pressure value remains constant. Alternatively, the second control stage can be divided into two consecutive pressure reduction stages and one low-pressure constant period, namely the first consecutive pressure reduction stage, the second consecutive pressure reduction stage, and the first low-pressure constant period, with the first low-pressure constant period located between the first and second consecutive pressure reduction stages. The continuous pressure reduction can be uniform and / or variable speed. Preferably, the number of consecutive pressure reduction stages is 2 to 5, i.e., the number of stages in the second control stage is 2 to 5. The purpose of staged pressure reduction is to prevent the complete vaporization of the primary foaming agent, which carries away a large amount of heat, making cross-linking and other reactions difficult to proceed at low temperatures. Staged pressure reduction ensures sufficient heat of reaction, thus balancing the closed-cell ratio and cross-linking density.
[0015] The polyols contained in the polyethers of this invention are compounds containing hydroxyl groups, such as polyether polyols and polyester polyols. These polyols can be obtained using conventional materials in the art, specifically polyol compounds prepared by ring-opening polymerization using compounds containing active hydrogen (such as polyols and / or polyamines) as initiators. Commonly used initiators in the art include trimethylolpropane, glycerol, pentaerythritol, triethanolamine, and aniline. Polyester polyols are typically formed by the condensation of organic dicarboxylic acids (anhydrides or esters) with small-molecule polyols (including diols) or by the polymerization of lactones with polyols. The dicarboxylic acids (anhydrides or esters) can be selected from phthalic anhydride, terephthalic acid, dimethyl terephthalate, adipic acid, etc., and the small-molecule polyols can be selected from ethylene glycol, propylene glycol, butanediol, propylene glycol monohydrate, trimethylolpropane, pentaerythritol, etc. The hydroxyl value of the polyols is typically 200–650 mg KOH / g. The catalyst can be any commonly used catalyst in the art, such as pentamethyldiethylenetriamine, bis(dimethylaminoethyl) ether, tetramethylhexanediamine, dibutyltin dilaurate, N-ethylmorpholine, N,N-dimethylcyclohexylamine, triethylenediamine, 1,2-dimethylimidazolium, dimethylbenzylamine, 1,3,5-tris(dimethylaminopropyl)hexahydrotriazine, 2,4,6-tris(dimethylaminomethyl)phenol, quaternary ammonium salts, potassium octanoate, potassium 2-ethylhexanoate, potassium acetate, (2-hydroxypropyl)trimethylammonium formate, ethyl quaternary ammonium salts, and octyl quaternary ammonium salts. When two or more catalysts are used, they can be mixed in any proportion.
[0016] The foam stabilizer used in the polyether combination of this invention is typically a polysiloxane-olefin oxide block copolymer, which can be selected from commercially available products, such as M-8805, M-8818, M-8825, M-8830, M-8860, M-8815, M-8806, M-8860, M-8882, M-88308, M-88310, and M-883 from Mester Chemicals. 12. Any one or more of Evonik B8465, B84725, B8486, B84204, B8404, B8407, B8409, B8110, Momentive Y16130, L5162, L6972, L6884, L6895, L6988, L6889, L6884, L6978, L6620, and L6972. When two or more foam stabilizers are selected, they can be mixed in any proportion.
[0017] The physical blowing agent described in this invention can be any conventional physical blowing agent in the art, such as one or more of alkane blowing agents, hydrofluorocarbon blowing agents, fluoroolefin blowing agents, carbon dioxide, and methyl formate. The alkane compounds are selected from, but not limited to, alkanes with boiling points from -45°C to 100°C, such as cyclopentane, isopentane, neopentane, n-pentane, n-butane, isobutane, cyclohexane, propane, n-hexane and its isomers, n-heptane and its isomers, etc. The hydrofluorocarbon blowing agent is selected from, but not limited to, pentafluoropropane, pentafluorobutane, difluoroethane, tetrafluoroethane, etc., and the fluoroolefin blowing agent can be selected from, but not limited to, monofluoropropylene, difluoropropylene, monofluorobutene, difluorobutene, trifluoropropylene, trifluorobutene, tetrafluorobutene, tetrafluoropropylene, pentafluoropropylene, hexafluoropropylene, hexafluorobutene, heptafluorobutene, octafluorobutene, octafluoropentene, or difluoroethylene, etc. Since hydrofluorocarbon foaming agents have high GWP values and are detrimental to the environment, this invention prefers environmentally friendly foaming agents, such as one or more of alkane foaming agents, fluoroolefin foaming agents, and methyl formate.
[0018] To further ensure a good closed-cell ratio, the present invention preferably includes a fluoroolefin blowing agent in the physical blowing agent. The fluoroolefin blowing agent may be selected from one or more of the following: cis-1-chloro-3,3,3-trifluoropropene, trans-1-chloro-3,3,3-trifluoropropene, cis-1,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, 2,3,3,3-tetrafluoropropene, 1,1,2,3,3-pentafluoropropene, hexafluoropropene, cis-1,1,1,4,4,4-hexafluoro-2-butene, trans-1,1,1,4,4,4-hexafluoro-2-butene, and cis-1-chloro-2,3,3,3-tetrafluoropropene.
[0019] The isocyanate used in this invention can be any conventional material in the art, typically an isocyanate with an average functionality >2. It can be polymethylene polyphenyl polyisocyanate (referred to as polymeric MDI), toluene diisocyanate (referred to as TDI), modified isocyanate, etc. When two or more isocyanates are used, they can be mixed in any proportion. Preferably, the polymeric MDI has an average functionality of 2.7 to 2.9 to balance the thermal conductivity of rigid polyurethane foam. The polymeric MDI with an average functionality of 2.7 can be selected from... PM200, 44v20L M20s, Any of PM2010, with an average functionality of 2.9, polymeric MDI can be selected from... M50 PM400 44V40L Any one of 2085. Industrially, TDI is typically a mixture of 2,4-toluene diisocyanate and 2,6-toluene diisocyanate. Depending on the mass percentage of 2,4-toluene diisocyanate in the mixture, it is usually classified as TDI-65, TDI-80, TDI-100, etc., all of which can be used in this invention. Modified isocyanate refers to a substance obtained by reacting a polyol with an isocyanate. The polyol used can be a polyether polyol using glycerol, ethylene glycol, diethylene glycol, pentaerythritol, etc. as initiators, or a phthalic anhydride polyester polyol, or a bio-based polyol. Bio-based polyols are polyol compounds prepared from soybean oil, castor oil, rapeseed oil, jatropha oil, olive oil, palm oil, or derivatives of the above substances, such as castor oil polyol, olive oil polyol, palm oil polyol, castor oil derivative polyol, etc.
[0020] The amounts of the combined polyether and isocyanate components described in this invention are typically determined based on the isocyanate index. The isocyanate index is the ratio of the molar amount of reactive groups (i.e., NCO groups) in the isocyanate component to the molar amount of reactive groups (i.e., OH groups) in the combined polyether. Typically, the isocyanate index is 1.03–1.4. To match the polyol component of this application, the isocyanate index is preferably 1.05–1.25, meaning the ratio of the molar amount of reactive groups in the isocyanate to the molar amount of reactive groups in the combined polyether is 1.05–1.25. The raw materials used in this invention, by weight, are combined polyether : physical blowing agent : isocyanate = (104–110) : (17–39) : (94–141).
[0021] A second objective of this invention is to provide a composite polyether containing a polyol, a catalyst, a foam stabilizer, and water. The hydroxyl value of the composite polyether used in this invention can be within the range commonly used in the art, such as 300–600 mg KOH / g. To match the preparation method of this invention, the average hydroxyl value of the composite polyether is preferably 350–500 mg KOH / g, and the water content is ≤1.2 wt%, to provide suitable reactivity and ensure sufficient exothermic reaction. Water can react with isocyanates to produce carbon dioxide; therefore, water is commonly referred to as a chemical foaming agent. Studies have found that excessive carbon dioxide produced by the water reaction can disrupt the formation of micronuclei in the second control stage of this invention. However, not using water is also detrimental to micronucleus formation. Therefore, the water content of the composite polyether is controlled within the range of ≤1.2 wt%, more preferably ≤1.0 wt%.
[0022] The water content described in the invention includes the water naturally present in the raw materials constituting the polyether and additionally added water.
[0023] To be compatible with the preparation method of the present invention, the combined polyether of the present invention comprises the following substances in weight percentage:
[0024] The polyether composition contains 91–96 wt% polyol, 1.5–5.0 wt% catalyst, and 2.0–4.0 wt% foam stabilizer, with a water content of 0.2–1.2 wt%.
[0025] Furthermore, the applicant discovered through research that the type of polyol also affects the formation of micronuclei in the second control stage. For example, primary hydroxyl compounds, polyether polyols with amine compounds as initiators, and phthalic anhydride polyester polyols all have high reactivity with isocyanates, which in turn increases the crosslinking rate of the reactants in the first control stage. In order to ensure a suitable reaction rate in the first control stage while taking into account the closed-cell rate, it is preferred that the combined polyether contains at least one of primary hydroxyl compounds, polyether polyol I, and phthalic anhydride polyester polyol.
[0026] The primary hydroxyl compounds described in this invention are substances whose molecular chain segments contain primary hydroxyl (-CH2-OH) functional groups, such as EO-type polyethers prepared using only ethylene oxide as the olefin oxide component, EO-terminated polyethers using ethylene oxide as the end-capping component, BO-type polyether polyols prepared using only tetrahydrofuran as the olefin oxide component, BO-terminated polyethers using tetrahydrofuran as the end-capping component, and adipic acid polyester polyols, etc. To obtain a better micro-core effect, it is preferable that the content of the primary hydroxyl compound in the combined polyether is ≤20.1 wt%, such as 4.6–20.1 wt%.
[0027] The polyether polyol I described in this invention is a polyether polyol prepared using an amine compound as an initiator. The amine compound can be an amine and / or an alkanolamine, such as ethylenediamine, toluenediamine, diethanolamine, triethanolamine, diethylenetriamine, etc. To balance crosslinking speed and curing speed, the content of polyether polyol I in the composite polyether is preferably ≤15.1 wt%, and can be 4.6–15.1 wt%.
[0028] To balance micropore formation and foam strength, the proportion of phthalic anhydride polyester polyol in the composite polyether is preferably ≤20.3wt%, such as 2.8~20.3wt%.
[0029] Preferably, the polyether composition contains the following components by weight percentage: 4.5–15.1 wt% polyether polyol I, 0–20.1 wt% primary hydroxyl compound, 0–20.3 wt% phthalic anhydride polyester polyol, 57.6–85.6 wt% other polyether polyols, 1.5–5.0 wt% catalyst, 2.0–4.0 wt% foam stabilizer, 0–0.87 wt% added water, and 0–0.9 wt% nucleating agent. The other polyether polyols refer to polyether polyols that do not contain primary hydroxyl groups and are not classified as polyether polyol I, such as polyether polyols whose olefin oxide component does not contain ethylene oxide, or polyether polyols containing ethylene oxide but not end-capped with ethylene oxide, such as polyol compounds obtained by ring-opening polymerization using a polyhydroxy compound as an initiator. The polyhydroxy compound can be selected from trimethylolpropane, glycerol, mannitol, sorbitol, pentaerythritol, sucrose, xylitol, etc. The present invention can obtain good foam performance using the above-mentioned polyether polyols.
[0030] A third objective of this invention is to provide a polyurethane foam prepared using the combined polyether and preparation method of this invention. The resulting polyurethane foam has a pore size ≤ 50 μm and a closed-cell ratio > 95%, exhibiting extremely low thermal conductivity, which can significantly reduce energy consumption in end-use applications. More preferably, the pore size is ≤ 30 μm, such as 2–30 μm, to balance a high closed-cell ratio and extremely low thermal conductivity.
[0031] The present invention has the following advantages:
[0032] 1. The preparation method of this invention can achieve extremely small cell diameters. In the conventional preparation of polyurethane, nucleating agents are usually required to obtain fine bubble nuclei. Nucleating agents available in the art include fluorinated compounds (such as fluorinated alkyl ethers), carbon nanotubes, gel materials, and inorganic oxide particles. However, this application achieves good micro-nucleation without the use of nucleating agents. This invention achieves personalized control of the foaming process through cavity control, allowing for controlled vaporization of the physical foaming agent and the formation of numerous micro-nuclei without affecting material flowability and filling properties, ultimately resulting in extremely small cell diameters with an average pore size ≤50μm.
[0033] 2. The preparation method of the present invention can promote the formation and stability of micronuclei, while taking into account a high closed-cell ratio. Through the combined effect of the first and second controls, polyurethane foam with small pore size and high closed-cell ratio is obtained, thereby greatly improving the thermal insulation performance of polyurethane foam material, with a thermal conductivity of only 12-14 mW / (m·K).
[0034] 3. The polyurethane foam obtained by this invention also has good compressive strength and dimensional stability, and the overall performance of the foam is excellent. Detailed implementation method:
[0035] To better understand the present invention, the following embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.
[0036] The raw materials used in this invention are as follows:
[0037] Primary hydroxyl compound A, self-made, EO type polyether polyol, with polyether and glycerol as initiators, ethylene oxide as the oxidized olefin component, and hydroxyl value of 255 mgKOH / g;
[0038] Primary hydroxyl compound B, self-made, EO-terminated polyether polyol, with sucrose and diethylene glycol as initiators, olefin oxide components being propylene oxide and ethylene oxide, and hydroxyl value of 340 mgKOH / g;
[0039] Primary hydroxyl compound C, self-made, BO type polyether polyol, with sorbitol as the initiator, tetrahydrofuran as the oxidized olefin component, and a hydroxyl value of 360 mgKOH / g;
[0040] Primary hydroxyl compound D, self-made, BO-terminated polyether polyol, with sucrose and glycerol as initiators, propylene oxide and tetrahydrofuran as oxidized olefin components, and a hydroxyl value of 400 mg KOH / g;
[0041] Primary hydroxyl compound E, commercially available; hexamethylene adipic acid, hexanediol, polyester polyol P1106, Meirui New Materials, hydroxyl value 200mgKOH / g;
[0042] Polyether polyol I-1, self-made, with diethylenetriamine as the initiator, propylene oxide as the olefin oxide component, and a hydroxyl value of 648 mgKOH / g;
[0043] Polyether polyol I-2, self-made, with triethanolamine as the initiator, propylene oxide as the olefin oxide component, and a hydroxyl value of 240 mgKOH / g;
[0044] Polyether polyol I-3, commercially available, o-toluenediamine polyether polyol, Voranol TM 391, Dow Chemical, hydroxyl value is 391 mg KOH / g;
[0045] Phthalic anhydride polyester polyol, commercially available, HF-8020, Huafeng Group, hydroxyl value 200mgKOH / g.
[0046] Other polyether polyols:
[0047] Voranol TM 360, Dow Chemical, the initiators are sucrose and glycerol, the olefin oxidation component is propylene oxide, and the hydroxyl value is 360 mg KOH / g;
[0048] ZS-4110, Zhongshan Chemical, uses sucrose and diethylene glycol as initiators, propylene oxide as the oxidizing olefin component, and has a hydroxyl value of 430 mgKOH / g.
[0049] Voranol TM 550, Dow Chemical, the initiator is sucrose and glycerol, the olefin oxidation component is propylene oxide, and the hydroxyl value is 550 mg KOH / g;
[0050] H5021, Hongbaoli Group, with sorbitol as the initiator, propylene oxide as the olefin oxidation component, and a hydroxyl value of 360 mgKOH / g;
[0051] H6020, Hongbaoli Group, with sorbitol as the initiator, propylene oxide as the oxidizing olefin component, and a hydroxyl value of 400 mg KOH / g;
[0052] H305, Hongbaoli Group, uses glycerol as the initiator, propylene oxide as the oxidized olefin component, and has a hydroxyl value of 335 mg KOH / g.
[0053] The self-made polyether polyol of this invention is produced using the method described in CN114225882A. Specifically, for EO-terminated polyethers, the order of addition is to add all or part of the ethylene oxide monomer last to continue the reaction, resulting in primary hydroxyl groups at the end; for BO-terminated polyethers, the order of addition is to add all or part of the tetrahydrofuran monomer last to continue the reaction, resulting in primary hydroxyl groups at the end.
[0054] Catalysts: Polycat 35 (Evonik), Dabco R-8020 (Air Products), Polycat 41 (Evonik).
[0055] The polyurethane foam preparation method of the present invention can specifically adopt one of the following methods:
[0056] Method 1:
[0057] Premixed polyether and physical blowing agent are premixed to obtain premix I. The temperature of premix I is controlled at 5–70°C, and then mixed with isocyanate at 15–25°C using a two-component nozzle at high speed. The mixture is then injected into a mold with dimensions of 400×400×80mm and a temperature of 30–50°C. The mold cavity is first controlled from the start of mixture injection, and a second control is performed after the first control is completed. Polyurethane foam is obtained after the reaction product has cured and formed.
[0058] Method 2:
[0059] Premix I is obtained by premixing a polyether and a high-boiling-point blowing agent (boiling point > 0℃). Premix II is obtained by premixing a low-boiling-point blowing agent (boiling point ≤ 0℃) with isocyanate. The temperature of premix I is controlled at 5–70℃, and the temperature of premix II is controlled at 0–15℃. Then, premix I and premix II are mixed at high speed using a two-component nozzle and injected into a mold with dimensions of 400×400×80mm and a temperature of 30–50℃. The mold cavity is first controlled from the start of injection, and second controlled after the first control is completed. Polyurethane foam is obtained after the reaction product has cured and formed.
[0060] Method 3:
[0061] A premix of polyether and a high-boiling-point blowing agent (boiling point > 0℃) was obtained to form premix I. The temperature of premix I was controlled at 5–70℃, and the temperature of the isocyanate was controlled at 0–15℃. Pressure was applied to the low-boiling-point blowing agent (boiling point ≤ 0℃) to keep it in a liquid state. Then, premix I, isocyanate, and low-boiling-point blowing agent were mixed at high speed using a three-component nozzle and injected into a mold with dimensions of 400×400×80mm and a temperature of 30–50℃. The mold cavity was first controlled from the start of the mixture injection, and a second control was performed after the first control was completed. After the reaction product cured and solidified, polyurethane foam was obtained.
[0062] All pressures mentioned in this invention are gauge pressures. The average hydroxyl value is determined using the method specified in HG / T 4961-2016. The apparent core density, closed-cell ratio, compressive strength, thermal conductivity, and dimensional stability are determined using the method specified in GB / T 26689-2011. The average pore size is determined using the method specified in Appendix A of GB / T 8810-2005.
[0063] The formulations used in this invention for preparing polyurethane foam are shown in Tables 1 and 2.
[0064] Examples 1 to 12 illustrate the preparation process of the polyurethane foam of the present invention.
[0065] Comparative Examples 1 to 10 are examples that are compared with the polyurethane foam of the present invention.
[0066] Table 1: Formulas 1# to 8#
[0067]
[0068]
[0069] Table 2: Formulas for 9# to D-4#
[0070]
[0071]
[0072] Example 1
[0073] Polyurethane foam was prepared using Formulation #1 and Method 1. Primary hydroxyl compound, polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. The composite polyether was then mixed with a physical blowing agent to obtain premix I-1. The temperature of premix I-1 was controlled at 50°C, and then mixed with 25°C isocyanate using a two-component nozzle at high speed. The mixture was then injected into a mold at a temperature of 45°C and an internal pressure of 1.5 bar.
[0074] The mold cavity is first controlled when the mixture is injected. The duration of the first control period is 16.5s. The pressure at the end of the first control is 10 bar. The first control phase is intermittent and consists of 3 cycles. That is, three pressure increases are performed during the first control period. The first pressure is increased to 3.0 bar within 2s and held for 3s. Then, the pressure is increased to 6.0 bar within 2s and held for 3s. Finally, the pressure is increased to 10.0 bar within 2s and held for 4.5s.
[0075] After the first control period, a second control period is initiated, lasting 22 seconds, meaning it is completed within 70% of the gel time. This second control is intermittent, occurring four times: First, the pressure is reduced to 9.0 bar within 2 seconds and held for 3 seconds. Then, a second pressure reduction occurs, reducing the pressure to 6.0 bar within 2 seconds and holding for 3 seconds. Next, a third pressure reduction occurs, reducing the pressure to 2.0 bar within 2 seconds and holding for 3 seconds. Finally, a fourth pressure reduction occurs, reducing the pressure to -1.0 bar within 2 seconds and holding for 5 seconds. After the reaction product cures and solidifies, polyurethane foam, denoted as PU-1#, is obtained.
[0076] Example 2
[0077] Polyurethane foam was prepared using Formulation #2 and Method 1. Primary hydroxyl compound, polyether polyol I, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. The composite polyether was then mixed with a physical blowing agent to obtain premix I-2. The temperature of premix I-2 was controlled at 40°C, and then mixed with 25°C isocyanate using a two-component nozzle at high speed. The mixture was then injected into a mold at 45°C with an internal pressure of 0.9 bar.
[0078] The mold cavity is first controlled when the mixture is injected. The duration of the first control period is 20 seconds. The pressure at the end of the first control is 9.0 bar. The first control phase is intermittent and occurs twice. That is, two pressure increases are performed during the first control period. The first pressure is increased to 4.0 bar within 4 seconds and held for 6 seconds. Then, the pressure is increased to 5.0 bar within 5 seconds and held for 5 seconds.
[0079] After the first control period, a second control period is performed. The second control period lasts 17.5 seconds, meaning it is completed at 75% of the gel time. The second control period is intermittent, consisting of three depressurization operations. First, the pressure is reduced to 7.0 bar within 2 seconds and held for 4 seconds. Then, a second depressurization is performed, reducing the pressure to 4.0 bar within 2 seconds and holding for 4 seconds. Finally, a third depressurization is performed, reducing the pressure to -0.5 bar within 2 seconds and holding for 3.5 seconds. After the reaction product cures and solidifies, polyurethane foam is obtained, denoted as PU-2#.
[0080] Example 3
[0081] Polyurethane foam was prepared using formulation #3 and method two. Polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. This composite polyether was then mixed with cyclopentane to obtain premix I-3. Isobutane was premixed with isocyanate to obtain premix II-3. The temperature of premix I-3 was adjusted to 70°C, and the temperature of premix II-3 was adjusted to 5°C. The mixture was then stirred at high speed using a two-component nozzle and injected into a mold. The mold temperature was 50°C, and the internal pressure of the mold cavity was 2.0 bar.
[0082] The mold cavity is first controlled from the start of mixture injection. The duration of the first control period is 13.5 seconds, and the pressure at the end of the first control is 29.0 bar. The first control phase is continuous, meaning it follows the pressure-time curve during the first control period. Continuous boost control is performed.
[0083] After the first control period, a second control period is initiated, lasting 22.5 seconds, meaning it is completed at 80% of the gel time. This second control is intermittent, occurring four times: First, the pressure is reduced to 15.0 bar within 2 seconds and held for 4 seconds. Then, a second pressure reduction occurs, reducing the pressure to 8.0 bar within 2 seconds and holding for 3 seconds. Next, a third pressure reduction occurs, reducing the pressure to 4.0 bar within 2 seconds and holding for 3 seconds. Finally, a fourth pressure reduction occurs, reducing the pressure to 1.0 bar within 2 seconds and holding for 4.5 seconds. After the reaction product cures, polyurethane foam, denoted as PU-3#, is obtained.
[0084] Example 4
[0085] Polyurethane foam was prepared using formulation #4 and method two. Primary hydroxyl compound, polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, and foam stabilizer were mixed to obtain a composite polyether. Then, cyclopentane and trans-1-chloro-3,3,3-trifluoropropylene were mixed with the composite polyether to obtain premix I-4. n-Butane and isocyanate were premixed to obtain premix II-4. The temperature of premix I-4 was adjusted to 20°C, and the temperature of premix II-4 was adjusted to 25°C. The mixture was then stirred at high speed using a two-component nozzle and injected into a mold. The mold temperature was 40°C, and the internal pressure of the mold cavity was 1.5 bar.
[0086] The mold cavity is first controlled when the mixture is injected. The duration of the first control period is 16 seconds. The pressure at the end of the first control period is 17 bar. The first control phase is continuous, that is, the pressure is continuously increased according to the pressure-time curve P = 3.88t + 1.5 during the first control period.
[0087] After the first control period, a second control period is initiated, lasting 16 seconds, meaning it is completed at 80% of the gel time. This second control is intermittent, occurring four times: First, the pressure is reduced to 10.0 bar within 2 seconds and held for 2 seconds. Then, a second pressure reduction occurs, reducing the pressure to 5.0 bar within 2 seconds and holding for 2 seconds. Next, a third pressure reduction occurs, reducing the pressure to 3.0 bar within 2 seconds and holding for 2 seconds. Finally, a fourth pressure reduction occurs, reducing the pressure to 0.5 bar within 2 seconds and holding for 2 seconds. After the reaction product cures, polyurethane foam, denoted as PU-4#, is obtained.
[0088] Example 5
[0089] Polyurethane foam was prepared using Formulation #5 and Method 1. Primary hydroxyl compound, polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, and foam stabilizer were mixed to obtain a composite polyether. Then, a physical blowing agent was mixed with the composite polyether to obtain premix I-5. The temperature of premix I-5 was controlled at 20°C, and then mixed with isocyanate at 20°C using a two-component nozzle with high-speed stirring. The mixture was then injected into a mold at a temperature of 45°C and an internal pressure of 0.5 bar.
[0090] The mold cavity is first controlled from the start of the mixture injection. The duration of the first control period is 25 seconds, and the pressure at the end of the first control is 11 bar. The first control phase is continuous, meaning it follows the pressure-time curve P = 2.1t during the first control period. 2 +0.5 continuously performs boost control.
[0091] After the first control is completed, a second control is performed. The second control lasts for 12.5 seconds, meaning it is completed at 75% of the gel time. The second control is intermittent, performed three times. Specifically, three pressure reduction operations are performed during the second control: first, the pressure is reduced to 8.0 bar within 1 second and held for 3 seconds; then, the pressure is reduced to 3.0 bar within 1 second and held for 3 seconds; finally, the pressure is reduced to -0.1 bar within 1 second and held for 3.5 seconds. After the reaction product cures and solidifies, polyurethane foam is obtained, designated PU-5#.
[0092] Example 6
[0093] Polyurethane foam was prepared using Formulation #6 and Method 2. Polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. Then, the composite polyether was mixed with trans-1-chloro-3,3,3-trifluoropropylene to obtain premix I-6. Hexafluoropropylene was premixed with isocyanate to obtain premix II-6. The temperature of premix I-6 was adjusted to 60°C, and the temperature of premix II-6 was adjusted to 0°C. The mixture was then mixed using a two-component nozzle at high speed and injected into a mold. The mold temperature was 35°C, and the internal pressure of the mold cavity was 5.0 bar.
[0094] The mold cavity is first controlled from the start of the mixture injection. The duration of the first control period is 16 seconds, and the pressure at the end of the first control is 40 bar. The first control phase is continuous, meaning it follows the pressure-time curve during the first control period. Continuous boost control is performed.
[0095] After the first control period, a second control period is initiated, lasting 16 seconds, meaning it is completed within 80% of the gel time. This second control is intermittent, consisting of five cycles: First, the pressure is reduced to 30.0 bar within 2 seconds and held for 2 seconds. Second, the pressure is reduced to 15.0 bar within 1 second and held for 2 seconds. Third, the pressure is reduced to 7.0 bar within 1 second and held for 2 seconds. Fourth, the pressure is reduced to 5.0 bar within 1 second and held for 2 seconds. Finally, the pressure is reduced to 0.7 bar within 1 second and held for 2 seconds. After the reaction product cures, polyurethane foam, denoted as PU-6#, is obtained.
[0096] Example 7
[0097] Polyurethane foam was prepared using Formulation #7 and Method 3. Primary hydroxyl compound, polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. Then, the composite polyether was mixed with cyclopentane and trans-1-chloro-3,3,3-trifluoropropylene to obtain premix I-7. The temperature of premix I-7 was adjusted to 20°C, the isocyanate temperature to 10°C, and the trans-1,3,3,3-tetrafluoropropylene temperature to 0°C. The mixture was then stirred at high speed using a three-component nozzle and injected into a mold. The mold temperature was 40°C, and the pressure inside the mold cavity was 3.0 bar.
[0098] The mold cavity is first controlled from the start of the mixture injection. The duration of the first control period is 18 seconds, and the pressure at the end of the first control is 32 bar. The first control phase is continuous, meaning it follows the pressure-time curve during the first control period. Continuous boost control is performed.
[0099] After the first control period, a second control period was initiated, lasting 15.8 seconds, meaning it was completed at 75% of the gel time. This second control was intermittent, consisting of five cycles: First, the pressure was reduced to 25.0 bar within 2 seconds and held for 2 seconds. Second, the pressure was reduced to 15.0 bar within 1 second and held for 2 seconds. Third, the pressure was reduced to 8.0 bar within 1 second and held for 2 seconds. Fourth, the pressure was reduced to 3.0 bar within 1 second and held for 2 seconds. Finally, the pressure was reduced to 0.3 bar within 1 second and held for 1.8 seconds. After the reaction product cured, polyurethane foam, denoted as PU-7#, was obtained.
[0100] Example 8
[0101] Polyurethane foam was prepared using Formulation #8 and Method 3. Primary hydroxyl compound, polyether polyol I, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. The composite polyether was then mixed with cyclopentane to obtain premix I-8. The temperature of premix I-8 was adjusted to 40°C, the isocyanate temperature to 5°C, and the 2,3,3,3-tetrafluoropropylene temperature to 0°C. The mixture was then stirred at high speed using a three-component mixing nozzle and injected into a mold. The mold temperature was 40°C, and the pressure inside the mold cavity was 5.0 bar.
[0102] The mold cavity is first controlled from the start of mixture injection. The duration of the first control period is 18 seconds, and the pressure at the end of the first control is 36 bar. The first control phase is continuous, meaning it follows the pressure-time curve during the first control period. Continuous boost control is performed.
[0103] After the first control period, a second control period is initiated, lasting 13.5 seconds, meaning it is completed within 70% of the gel time. This second control is intermittent, occurring four times: First, the pressure is reduced to 28.0 bar within 3 seconds and held for 1.5 seconds. Then, a second pressure reduction occurs, reducing the pressure to 20.0 bar within 1 second and holding for 2 seconds. Next, a third pressure reduction occurs, reducing the pressure to 8.0 bar within 1 second and holding for 2 seconds. Finally, a fourth pressure reduction occurs, reducing the pressure to 1.3 bar within 1 second and holding for 2 seconds. After the reaction product cures, polyurethane foam, denoted as PU-8#, is obtained.
[0104] Example 9
[0105] Polyurethane foam was prepared using Formulation #9 and Method 1. Primary hydroxyl compound, polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. The composite polyether was then mixed with a physical blowing agent to obtain premix I-9. The temperature of premix I-9 was controlled at 5°C, and then it was mixed with 10°C isocyanate using a two-component nozzle with high-speed stirring. The mixture was then injected into a mold at a temperature of 45°C and the pressure inside the mold cavity was atmospheric pressure.
[0106] The mold cavity is first controlled when the mixture is injected. The duration of the first control period is 14s. The pressure at the end of the first control period is 13bar. The first control phase is continuous, that is, the pressure is continuously increased according to the pressure-time curve P = 3.47t during the first control period.
[0107] After the first control period, a second control period is initiated, lasting 12.3 seconds, meaning it is completed at 75% of the gel time. This second control is intermittent, occurring three times: First, the pressure is reduced to 8.0 bar within 2 seconds and held for 2.3 seconds. Then, a second pressure reduction occurs, reducing the pressure to 4.0 bar within 2 seconds and holding for 2 seconds. Finally, a third pressure reduction occurs, reducing the pressure to -1.0 bar within 2 seconds and holding for 2 seconds. After the reaction product cures and solidifies, polyurethane foam, denoted as PU-9#, is obtained.
[0108] Example 10
[0109] Polyurethane foam was prepared using Formulation 10 and Method 1. Primary hydroxyl compound, polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. The composite polyether was then mixed with a physical blowing agent to obtain premix I-10. The temperature of premix I-10 was controlled at 10°C, and then mixed with 20°C isocyanate using a two-component nozzle with high-speed stirring. The mixture was then injected into a mold at a temperature of 45°C and an internal pressure of atmospheric pressure.
[0110] The mold cavity is first controlled from the start of the mixture injection. The duration of the first control period is 14 seconds, and the pressure at the end of the first control is 11 bar. The first control phase is continuous, meaning that during the first control period, the pressure-time curve P = 2.94t is followed. 2 Continuous boost control is performed.
[0111] After the first control is completed, a second control is performed. The second control lasts for 14 seconds, meaning it is completed at 80% of the gel time. The second control is intermittent, performed three times. Specifically, three pressure reduction operations are performed during the second control: first, the pressure is reduced to 7.0 bar within 2 seconds and held for 3 seconds; then, the pressure is reduced to 3.0 bar within 2 seconds and held for 3 seconds; finally, the pressure is reduced to -0.8 bar within 2 seconds and held for 2 seconds. After the reaction product cures and solidifies, polyurethane foam is obtained, designated PU-10#.
[0112] Example 11
[0113] Polyurethane foam was prepared using Formulation 11 and Method 1. Primary hydroxyl compound, polyether polyol I, phthalic anhydride polyester polyol, other polyether polyols, catalyst, foam stabilizer, and added water were mixed to obtain a composite polyether. The composite polyether was then mixed with a physical blowing agent to obtain premix I-11. The temperature of premix I-11 was controlled at 25°C, and then mixed with isocyanate at 25°C using a two-component nozzle with high-speed stirring. The mixture was then injected into a mold at a temperature of 45°C and an internal pressure of 0.5 bar.
[0114] The mold cavity is first controlled from the start of the mixture injection. The duration of the first control period is 21 seconds. The pressure at the end of the first control is 14 bar. The first control phase is intermittent and consists of 4 cycles. That is, four pressure increases are performed during the first control period. The first pressure increase is performed within 2 seconds to 4.0 bar and held for 3 seconds. Then, the pressure increase is performed a second time to 8.0 bar within 2 seconds and held for 3 seconds. Then, the pressure increase is performed a third time to 12 bar within 2 seconds and held for 3 seconds. Finally, the pressure increase is performed a fourth time to 14.0 bar within 2 seconds and held for 4 seconds.
[0115] After the first control is completed, a second control is performed. The second control lasts for 7 seconds, meaning it is completed at 80% of the gel time. The second control is intermittent, performed twice. Specifically, two pressure reduction operations are performed during the second control: first, the pressure is reduced to 6.0 bar within 2 seconds and held for 2 seconds; then, the pressure is reduced to -0.5 bar within 2 seconds and held for 1 second. After the reaction product cures and solidifies, polyurethane foam, denoted as PU-11#, is obtained.
[0116] Example 12
[0117] The difference from Example 1 is that Formula 12 is used; otherwise, it is the same as Example 1.
[0118] Comparative Example 1
[0119] The difference from Example 1 is that the D-1# formula is used; otherwise, it is the same as Example 1.
[0120] Comparative Example 2
[0121] The difference from Example 1 is that the D-2# formula is used, otherwise it is the same as Example 1.
[0122] Comparative Example 3
[0123] The difference from Example 6 is the use of the D-3# formulation; otherwise, it is the same as Example 6.
[0124] Comparative Example 4
[0125] The difference from Example 11 is that the D-4# formula is used; otherwise, it is the same as Example 11.
[0126] Comparative Example 5
[0127] Formula #4 was used, but it differed from Example 4 in that the first and second controls were not performed. The polyurethane foam was prepared by placing the mold under normal pressure. Otherwise, it was the same as Example 4.
[0128] Comparative Example 6
[0129] Formula 12# is used, but it differs from Example 12 in that the first and second controls are not performed. The mold is foamed under normal pressure. Otherwise, it is the same as Example 12.
[0130] Comparative Example 7
[0131] The formula used is #7, which differs from Example 7 in that the pressure during the first control stage is always maintained at 3.0 bar; otherwise, it is the same as Example 7.
[0132] Comparative Example 8
[0133] Formula #7 is used, but it differs from Example 7 in that the second control stage does not use a graded pressure reduction method, but instead uses a single pressure reduction, that is, the pressure is reduced to 0.3 bar within 3 seconds after the first control ends. The rest is the same as Example 7.
[0134] Comparative Example 9
[0135] Formula #7 was used, but it differed from Example 7 in that the duration of the first control exceeded 60% of the gel time, and the end time of the second control was the same as in Example 7, i.e., the first control period was 30s and the duration of the second control was 3.8s. The rest was the same as in Example 7.
[0136] Comparative Example 10
[0137] Formula #7 was used, but it differed from Example 7 in that the duration of the second control was 22.5 s, meaning that the second control was completed at 90% of the gel time. The rest was the same as in Example 7.
[0138] The performance test results of the polyurethane foam prepared by this invention are shown in Tables 3 and 4.
[0139] Table 3 Performance characterization results of Examples 1-11
[0140]
[0141]
[0142] Table 4 Performance characterization results of Examples 12 and Comparative Examples 1-10
[0143]
[0144]
[0145] As can be seen from the data in the table, the preparation method of the present invention can obtain rigid polyurethane foam with extremely small pore size and high closed-cell ratio, with a thermal conductivity of only 12-14 mW / (m·K), and good performance in terms of compressive strength, dimensional stability and other properties, which can meet the needs of end applications.
[0146] Comparative Example 1 used a large amount of water, resulting in the generation of more carbon dioxide in the early stage, which was not conducive to the formation of micronuclei and increased the thermal conductivity. Comparative Examples 2, 3, and 4 all used a high proportion of highly active polyol raw materials, which caused the reaction rate in the first control stage to be too fast, leading to an imbalance between the vaporization rate and the reaction rate in the second control stage, which was not conducive to the formation of micronuclei, increased porosity, and increased thermal conductivity.
[0147] Comparative Example 5 used a conventional foaming method, resulting in the escape of low-boiling-point foaming agent from the material system, leading to foaming agent loss. The resulting rigid polyurethane foam had a high density, and the lack of control over cell growth resulted in larger cell sizes and higher thermal conductivity. Comparative Example 6 used a conventional foaming method in the presence of a nucleating agent, improving thermal conductivity somewhat, but still not as effectively as the method of this invention. Comparative Example 7, although controlling the pressure within the mold cavity in the first control stage, did not use sufficient pressure to keep the physical foaming agent in a liquid state throughout the first control stage, causing foaming agent loss and hindering micronucleus formation, ultimately resulting in poor improvement in thermal conductivity. Comparative Example 8, although performing the first control, reduced the pressure to the endpoint value all at once in the second control stage, removing a large amount of reaction heat, affecting the reaction process and hindering micronucleus formation, leading to increased thermal conductivity and porosity. Comparative Example 9, with its excessively long first control time, lacked sufficient time for the second control, resulting in increased porosity and higher thermal conductivity. The duration of the second control in Comparative Example 10 was too long, resulting in an increase in the porosity and thermal conductivity.
Claims
1. A method for preparing polyurethane foam, characterized in that, The process includes the following steps: injecting a mixture containing a polyether, a physical blowing agent, and an isocyanate into a cavity for reaction; subjecting the reaction process to first and second control; and obtaining polyurethane foam after the reaction product has solidified. The physical blowing agent remains in a liquid state during the first control period, which refers to 30-60% of the fiber time from the start of injection of the mixture. At the end of the first control, the pressure inside the cavity is greater than atmospheric pressure. The second control involves immediately reducing the pressure in stages at the end of the first control, with the number of stages being a natural number and ≥2. The pressure is reduced at each stage until the physical blowing agent can vaporize. The second control is completed before 70-80% of the fiber time of the mixture. The polyether composition has a water content of ≤1.2wt%, a primary hydroxyl compound content of ≤20.1wt%, a polyether polyol I content with amine compounds as initiators of ≤15.1wt%, a phthalic anhydride polyester polyol content of ≤20.3wt%, and a total polyol content of 91-96% of the polyether composition.
2. The preparation method according to claim 1, characterized in that, The pressure in the cavity gradually increases during the first control.
3. The preparation method according to claim 1, characterized in that, The number of levels is 2 to 5.
4. The preparation method according to claim 1, characterized in that, The physical foaming agent contains fluoroolefin compounds.
5. The preparation method according to claim 1, characterized in that, The ratio of the molar amount of reactive groups in the isocyanate to the molar amount of reactive groups in the combined polyether is 1.03 to 1.
4.
6. The preparation method according to claim 5, characterized in that, The ratio of the molar amount of reactive groups in the isocyanate to the molar amount of reactive groups in the combined polyether is 1.05 to 1.
25.
7. The preparation method according to claim 1, characterized in that, The mixture is prepared in the following weight ratio: polyether: physical foaming agent: isocyanate = (104~110): (17~39): (94~141).
8. A combined polyether used in the preparation method according to any one of claims 1 to 7, characterized in that, The polyether composition comprises the following substances by weight percentage: 91-96 wt% polyol, 1.5-5.0 wt% catalyst, and 2.0-4.0 wt% foam stabilizer. The content of primary hydroxyl compounds in the polyether composition is ≤20.1 wt%, the content of polyether polyol I with amine compounds as initiators in the polyether composition is ≤15.1 wt%, the proportion of phthalic anhydride polyester polyol in the polyether composition is ≤20.3 wt%, and the water content of the polyether composition is ≤1.2 wt%.
9. The composite polyether according to claim 8, characterized in that, The average hydroxyl value of the polyether combination is 300~600 mgKOH / g.
10. The composite polyether according to claim 9, characterized in that, The average hydroxyl value of the polyether combination is 350~500 mgKOH / g.
11. The composite polyether according to claim 8, characterized in that, The water content of the polyether composition is 0.2~1.2wt%.
12. A polyurethane foam prepared by the method according to any one of claims 1-7, characterized in that, The polyurethane foam has a pore size ≤ 50 μm and a closed-cell rate ≥ 95%.
Citation Information
Patent Citations
Refrigerator, rigid polyurethane foam and preparation method of rigid polyurethane foam
CN112175158A
Process for preparing rigid polyurethane foams
CN1995109A
Urethane resin composition and polyurethane foam
JP2024139567A